Skrining Actinomycetes Penghasil L-asparginase dari Pantai Olo, Sumatera Utara dan Uji Aktivitas Enzim - Hartini, Martha Yeni Sry; Yurnaliza; Hastuti, Liana Dwi Sri (Department of Biology Education, FSTT, Mandalika University of Education, Indonesia., 2025)
This research aims to isolate actinomycetes that produce the enzyme L-asparaginase from Olo Beach and to determine the activity of the L-asparaginase enzyme produced. Actinomycetes producing the enzyme L-asparaginase were obtained through the following steps: isolation on SCA medium using the spread plate method; selection of L-asparaginase-producing actinomycetes on M-9 liquid medium with phenol red as a color indicator; production of L-asparaginase based on the principle of fermentation in production medium, followed by measurement of L-asparaginase activity and protein content. Protein content was determined using the Lowry method with Bovine Serum Albumin (BSA) as the standard. The data obtained were analyzed using ammonia and BSA standard curves. The results showed that 11 actinomycetes isolates from Olo Beach were capable of producing L-asparaginase. Qualitative selection showed a change in media color from yellow to pink, indicating the presence of L-asparaginase activity. Quantitatively, the highest L-asparaginase enzyme activity was 40.688 U/mL and the highest specific activity was 123,677 U/mg, found in isolate SPO 6. The lowest enzyme activity was 31,651 U/mL and the lowest specific activity was 25,874 U/mg. Specific activity is influenced by enzyme activity and protein content.